Shall we dance (Distributed by Warner Home Video, 2005)
A ballet star (Astaire) and a musical revue sensation (Rogers) decide to wed and publicly divorce to quash persistent rumors of a secret marriage. Once tied, however, perhaps they shouldn't call the whole thing off.